"Com a pena educo, com o prelo torno-me autora": Ellen G. White e a pedagogia da medicina temperante (1827-1915) - Sousa, Débora da Silva (2019)
United States. 1827-1915. During this almost century, lived the author Ellen Gould White, Seventh-Day Adventist. This woman could have been limited by the places that nineteenth-culture forced to her “gender”. Certainly, mother, wife and Protestant who, with her bible in his arms, moved from home to church, from church to home. However, even if exercising this functions in a not very common way, she preferred the world of spoken words, from the pulpit and the spoken speech, but, about everything, in the universe of written culture, where, incidentally, made crossings through deviant spaces when she treated her pen of themes that where not her own and only pertinent to the male fist and academic training. I am referring to the discussions about knowledge and erudite medical pratices of this temporal cut. Henceforth, through the writing and the press, the writer was exercising the “author-role” inside these sayings and writings, which only the “doctors” could refute, model and build. For how much, the aim of this thesis is to problematize the lines, the actions and the texts emanated by this female voice that unveiled, by means of her printed writing, her daring to question the “arts” of curing the body proposed by the nineteenth-century medicine, starting from the elaboration of a pro-health reform, and by the proposition of doctor’s education and the formation of a new profile of this professional in the ways of medicating. Printing script who the signature prepared for the Adventist places, seen with distrust by this protestant peers, for being the fist that produced this audacious thing, for electing scientific medicine and the certified Aesculapius to model and instruct. In order to do so, i’ve been listed as documentary corpus the pedagogical manuals dealing with health and its dialogues with medicine elaborated by the author, added by her autobiographical writings, in which the articulation of these historical discoveries allowed me to understand how this authorship have been consolidated. For this, I used the Authorship category, casted by Roger Chartier (1990; 1998, 1999; 2004; 2009; 2011; 2012; 2014) and other concepts which articulates with the “author-role”, like Reading, Appropriation, Reading Protocols and Translation. I also have appropriated of Michel Foucault’s “Heterotopia” and “Self-Written” (1992; 2006) to think of this author’s place as deviation from required standard for the women writing dedicated to the productions of good conduction guides to be printed. In this way, it was possible to me how a woman without formal education have the ambition to instruct through the writing the subjects that have the medical knowledge.